Improving Student Learning Outcomes in Arabic Learning Through the Think Pair Share (TPS) Model - Sumita Sabilla; Akmal Walad Ahkas (Edumaspul: Jurnal Pendidikan, 2023)
Abstract In teaching and learning activities, many factors are associated with student learning outcomes. One of them is the learning model. Processes to improve student learning outcomes in the learning process can be formed through the Think-Pair-Share Cooperative Learning model because Student-centered learning and requires them to independently complete case studies and share knowledge. This study aimed to improve student learning achievements after the cooperative learning models applied the type a Think-Pair-Share on the subject Bahasa Arab Minat : Fi’il Shahih, Mu’tal, and Fi’il Madhi in X-IIK 1 MAN 1 Medan. This type of research is Classroom Action Research. This research was conducted in two cycles, the cycle I use pre-test and reflection, the cycle II using post-test. Data obtained from this research analyzed by qualitative descriptive method. The results of this research is by implementing learning model Think-Pair-Share (TPS) can improve student learning outcomes. This is demonstrated by the growing results of learning, at the pre-test of 35 students, there are only a few students who reach a minimum SKM ≥ 76, cycle I increased to 25 from 35 students who achieve a percentage value of the SKM class completeness 71% and the cycle II, rose to 33 from 35 students to reach a value of ≥76 SKM percentage completeness the class of 94%. The response of students in learning using learning model Think-Pair-Share of 84%. Keywords: Think-Pair-Share Model, Learning Of Arabic, improve learning results, Classroom Action Research Abstrak Dalam kegiatan belajar mengajar, banyak faktor yang berhubungan dengan hasil belajar siswa. Salah satunya adalah model pembelajaran. Proses untuk meningkatkan hasil belajar siswa dalam proses pembelajaran dapat dibentuk melalui model Think-Pair-Share Cooperative Learning karena pembelajaran berpusat pada siswa dan mengharuskan mereka untuk secara mandiri menyelesaikan studi kasus dan berbagi pengetahuan. Penelitian ini bertujuan untuk meningkatkan prestasi belajar siswa setelah model pembelajaran kooperatif menerapkan tipe a Think-Pair-Share pada subjek Bahasa Arab Minat : Fi'il Shahih, Mu'tal, dan Fi'il Madhi pada X-IIK 1 MAN 1 Medan. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Penelitian ini dilakukan dalam dua siklus, yaitu siklus I menggunakan pre-test dan refleksi, siklus II menggunakan post-test. Data yang diperoleh dari penelitian ini dianalisis dengan metode deskriptif kualitatif. Hasil penelitian ini adalah dengan menerapkan model pembelajaran Think-Pair-Share (TPS) dapat meningkatkan hasil belajar siswa. Hal ini ditunjukkan dengan semakin berkembangnya hasil pembelajaran, pada pre-test 35 siswa hanya ada beberapa siswa yang mencapai SKM minimal ≥ 76, siklus I meningkat menjadi 25 dari 35 siswa yang mencapai nilai persentase ketuntasan kelas SKM 71% dan siklus II, naik menjadi 33 dari 35 siswa mencapai nilai ≥76 SKM persentase ketuntasan kelas 94%. Respon siswa dalam pembelajaran menggunakan model pembelajaran Think-Pair-Share sebesar 84%. Kata kunci: Model Pembelajaran Think-Pair-Share, Pembelajaran Bahasa Arab, hasil belajar, Penelitian Tindakan Kelas